A genre Analysis of the Scholarly Electronic Mail: Implications for Pedagogy - Malandi, Anne Bancy; Maroko, Geoffrey Mokua (University of Isfahan, 2018)
Scholarly mails apparently display stable conventional principles as an emerging genre. Thus, contributors should structure their electronic mails appropriately when writing for purposes of discussing professional topics. However, this requirement plunges many a scholar in dilemma as to how to go about this vital undertaking without written structural norms in electronic mail communication. This raises the question: what is the generic structure of the scholarly electronic mail? The aim of this paper therefore is to uncover the organizational structure of the scholarly electronic mail as an emerging genre of computer mediated discourse. A qualitative approach is adopted in the description of the generic structure. Through purposive and stratified sampling, twenty scholarly electronic mails were selected and closely studied based on the basic electronic schema model by Herring (1996) with a view to extracting the features of the genre. Findings revealed that the scholarly electronic mail has a generic structure which is signalled by typical linguistic elements. The paper recommends a genre-based approach to guiding upcoming scholars on how to construct a scholarly electronic mail that fulfils its communicative purposes.
Keywords: Generic Structure; Virtual Discourse Community; Macro Segments; Discussants; Reactive Mail; Schema